2005
DOI: 10.1002/cne.20429
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed transcripts from phenotypically identified olfactory sensory neurons

Abstract: In comparing purified mouse olfactory sensory neurons (OSNs) with neighboring cells, we identified 54 differentially expressed transcripts. One-third of the transcripts encode proteins with no known function, but the others have functions that correlate with challenges faced by OSNs. The OSNs expressed a diversity of signaling protein genes, including stomatin (Epb7.2), S100A5, Ddit3, Sirt2, CD81, Sdc2, Omp, and Ptpla. The elaboration of dendrites, cilia, and axons that places OSNs in contact with diverse cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 76 publications
3
87
0
1
Order By: Relevance
“…Ano2 transcripts are highly expressed in the olfactory system (GNF Symatlas and Genepaint), specifically in OSNs (20). Using independent in situ hybridization probes, we confirmed that Ano2 mRNA localized specifically to OSNs within the OE and not to the sustentacular or basal stem cell layers (Fig.…”
Section: Ano2 Is Present In a Preparation Of Olfactory Cilial Membranessupporting
confidence: 65%
See 1 more Smart Citation
“…Ano2 transcripts are highly expressed in the olfactory system (GNF Symatlas and Genepaint), specifically in OSNs (20). Using independent in situ hybridization probes, we confirmed that Ano2 mRNA localized specifically to OSNs within the OE and not to the sustentacular or basal stem cell layers (Fig.…”
Section: Ano2 Is Present In a Preparation Of Olfactory Cilial Membranessupporting
confidence: 65%
“…S6 and Table S3 ), ANO2 was the only ANO protein found in our proteomic screen. Additionally, no other Ano family member transcripts have been found to be OSN-specific (20). Bestrophin 2 (Best2) has been proposed as a candidate olfactory CaCC (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, both SUS1 and nestin antibodies also label cells of Bowman's glands, which lie within the lamina propria of the OE, suggesting that Bowman's gland epithelial cells and SUS cells may share a common progenitor, as has been hypothesized previously [9,22]. Other reports also indicate that SUS cells and respiratory epithelium share some antigenic properties [25], suggesting that SUS cells may not be part of the OE neural lineage.…”
Section: Sustentacular Cell Originsmentioning
confidence: 73%
“…This selfrenewing, non-neuronal cell type expresses enzymes involved in metabolizing foreign compounds (cytochrome p450, glutathione-S-transferase mu 2, and carbonyl reductase 2; [25]), suggesting a role for SUS cells in detoxifying many of the noxious substances present in the air, to which the OE is exposed. SUS cells also phagocytose dead ORNs [26], and much like the glia of the brain, probably provide structural support to ORNs.…”
Section: Sustentacular Cell Originsmentioning
confidence: 99%
“…The family of TMEM16 (alias: anoctamin) proteins have recently been shown to form Ca 2+ -activated Cl − channels (7,(21)(22)(23)(24). The mRNA of this protein was located in rodent ORNs (8,25), and TMEM16B is the only of the 10 TMEM16 isoforms present in the ciliary proteome (8,20). We detected the mRNA expression of TMEM16B in cDNA obtained from ORNs that were FACS purified.…”
Section: Nkcc1 Expressionmentioning
confidence: 99%